STRUCTURAL AND SEMANTIC FEATURES OF ANCIENT COMMON ROOTS IN TURKIC LANGUAGES - Kassym, Balkiya; Buran, Ahmet (My University, 2021)
This article is a diachronic study of the lexico-semantic sphere. The semantic field is the words that derive from the same root, belong to the same semantic field, and are formed as a result of the development of a certain root in various ways in the language system. In the study, the root words as (meal), köz (eye) and kör- (to see) and the words derived from them have been analyzed structurally. In the Kazakh language, examples of such words are the verbs ‘kör-egen-dik’ etc. ‘Astık, közde, köregen’ and similar words in Kazakh Turkish are some of the words derived from these roots. Many of the lexemes of this class are capable of forming verbs, nouns, etc. by adding various affixes. Thus, emphasising common Turkic roots for the Kazakhlanguage or other grounds, we can determine the derived words of the same root. In this study, the common and different meanings of the above-mentioned words in Turkic languages were determined, and the words derived from these roots and their usage areas in Turkic languages are presented.
Keywords: Dil ve Dil Bilim